Kajian Pembuatan Program Aplikasi Analisis Struktur Gedung Terhadap Beban Gempa Menggunakan Borland Delphi 6 - Aji, Seno (JURNAL AGRI-TEK, 2015)
Indonesia is a country often occurring earthquakes because most of the islands of indonesia situated in regions that have the activity of the earthquake are enough high because indonsia areas located at the confluence of three main plates of the world namely indo-australia plates, eurasian and pacific. To research will be done the study analysis of the structure on the burden of building earthquake use borland delphi 6 with studies the structure of the building floors 4 which are located in the madiun with force concrete (fc) used is 25 MPa and yield strength for steel (fy) that is used is 320 MPa. The purpose of this research is to calculate the value of a shearing force the average the layer of soil, the burden of nominal basic sliding horizontally because of earthquake that work on the structure building, the distribution of the burden of high earthquake building along, time a trill fundamental natural structure, and performance service limits the structure of the building with used the results of the program design using language programming delphi 6. To analysis of the structure on the burden of earthquake used SNI 1726 2002. The results of design application program using borland delphi 6 shows that the results of the value of obtained have a value by a similar. The difference in the value of the results could happen if the data included data is the result of rounding.Keywords: Borland Delphi 6, application program, analysis of the structure, the burden of building earthquake.